2004
DOI: 10.1055/s-2004-827145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Mycological Evaluation of Therapeutic Effectiveness ofSolanum chrysotrichumStandardized Extract on Patients withPityriasis capitis(Dandruff). A Double Blind and Randomized Clinical Trial Controlled with Ketoconazole

Abstract: Dandruff (also called Pityriasis capitis) is a seborrhoeic dermatitis of the scalp. It has been correlated with the pathological colonization of the scalp with yeast from the genus Malassezia; this illness has a worldwide distribution and represents 25% of all scalp dermatosis cases. It has been demonstrated that the extract obtained from leaves of the plant Solanum chrysotrichum possesses biological activity against dermatophytes and yeast. Different steroidal saponins with antimycotic activity have been isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Susceptibility of Candida strains to SC-2 was as follow: C. albicans = C. lusitaniae > C. krusei > C. glabrata. These results, combined with the previous reports of SC-2 against reference strains of C. albicans, and against Malassezia yeast associated with Pityriasis capitis, increase the SC-2 antifungicidal spectrum [4], [6]. IC 50 and MFC detected for SC-2 are higher than those reported for the anftifungals used as controls; nevertheless, it is important to note that a standardized herbal medicinal product from S. chrysotrichum would be elaborated with an extract enriched with SC-2 and other saponins with proven antifungal activity, with which a SC-2 activity-associated synergystic effect is obtained.…”
Section: Original Papersupporting
confidence: 73%
See 1 more Smart Citation
“…Susceptibility of Candida strains to SC-2 was as follow: C. albicans = C. lusitaniae > C. krusei > C. glabrata. These results, combined with the previous reports of SC-2 against reference strains of C. albicans, and against Malassezia yeast associated with Pityriasis capitis, increase the SC-2 antifungicidal spectrum [4], [6]. IC 50 and MFC detected for SC-2 are higher than those reported for the anftifungals used as controls; nevertheless, it is important to note that a standardized herbal medicinal product from S. chrysotrichum would be elaborated with an extract enriched with SC-2 and other saponins with proven antifungal activity, with which a SC-2 activity-associated synergystic effect is obtained.…”
Section: Original Papersupporting
confidence: 73%
“…This compound has significant inhibitory concentrations (IC 50 ) against reference strains of Candida albicans and dermatophytes in vitro [4]. In addition, two controlled clinical trials have demonstrated the effectiveness and therapeutic tolerability of herbal medicinal products elaborated from S. chrysotrichum, standardized in its content of active principles, in Malassezia yeast-associated Pityriasis capitis and Tinea pedis treatment [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Plant DNA assigning to the families Cannabaceae, Ranunculaceae, and Solanacea, which are known to contain medicinally important species, were also recovered. However to resolve these sequences beyond the family level another gene region would need to be targeted, and this might reveal, for example, whether the Solanaceae (Nightshade family) identified in four of the TCM samples comprised S. chrysotrichum (Giant Devil's Fig) which has known pharmacological activity [62], or perhaps the less exotic species such as potato or tomato.…”
Section: Resultsmentioning
confidence: 99%
“…36 was the most active in indicating fungicidal effect against Candida albicans and non-albicans strains [113, 114, 117]. …”
Section: Chemical Constituents and Their Biological Propertiesmentioning
confidence: 99%